Effectiveness of Stroke Early Supported Discharge: Analysis From a National Stroke Registry. Issue 8 (August 2020) - Fisher, Rebecca J.; Byrne, Adrian; Chouliara, Niki; Lewis, Sarah; Paley, Lizz; Hoffman, Alex; Rudd, Anthony; Robinson, Thompson; Langhorne, Peter; Walker, Marion F.
Abstract : Background: Implementation of stroke early supported discharge (ESD) services has been recommended in many countries' clinical guidelines, based on clinical trial evidence. This is the first observational study to investigate the effectiveness of ESD service models operating in real-world conditions, at scale. Methods and Results: Using historical prospective data from the United Kingdom Sentinel Stroke National Audit Programme (January 1, 2016–December 31, 2016), measures of ESD effectiveness were "days to ESD" (number of days from hospital discharge to first ESD contact; n=6222), "rehabilitation intensity" (total number of treatment days/total days with ESD; n=5891), and stroke survivor outcome (modified Rankin scale at ESD discharge; n=6222). ESD service models (derived from Sentinel Stroke National Audit Programme postacute organizational audit data) were categorized with a 17-item score, reflecting adoption of ESD consensus core components (evidence-based criteria). Multilevel modeling analysis was undertaken as patients were clustered within ESD teams across the Midlands, East, and North of England (n=31). A variety of ESD service models had been adopted, as reflected by variability in the ESD consensus score. Controlling for patient characteristics and Sentinel Stroke National Audit Programme hospital score, a 1-unit increase in ESD consensus score was significantly associated with a more responsive ESD service (reduced odds of patient being seen after ≥1 day of 29% [95% CI, 1%–49%] and increased treatment intensity by 2% [95% CI, 0.3%–4%]). There was no association with stroke survivor outcome measured by the modified Rankin Scale. Conclusions: This study has shown that adopting defined core components of ESD is associated with providing a more responsive and intensive ESD service. This shows that adherence to evidence-based criteria is likely to result in a more effective ESD service as defined by process measures. Registration: URL: http://www.isrctn.com/ ; Unique identifier: ISRCTN15568163. Abstract : Supplemental Digital Content is available in the text.